Leukocytary changes in patients with COVID-19 observed in peripheral blood extension (Research, Society and Development, 2021)
The aim of the study was to verify the main alterations in the leukocyte lineage caused by infection with SARS-CoV-2, a virus of zoonotic origin responsible for the disease known as COVID-19. SARS-CoV-2 affects several systems, including the hematopoietic system, which causes changes in leukocyte lineages. Patients infected with the SARS-CoV-2 virus had numerical and morphological alterations in the leukocyte lineage, with lymphopenia and neutrophilia being more significant. As for morphology, several anomalies were observed. Plasmacytoid and Downey cell-like reactive lymphocytes were frequently observed. Dysplastic monocytes and hypolobulated neutrophils, classified as acquired Pseudo Pelger-Huet anomaly, were also present. These abnormalities were correlated with a greater chance of admission to the ICU and progression to death. There was a correspondence between the normal eosinophil count and the positive progression of the disease, suggesting that eosinophil regeneration is related to disease recovery. This set of changes has not been observed in any other viral pneumonia. The differential leukocyte count is a quick and easy test to perform, which can help the medical team to classify patients with serious or non-serious conditions, and provide guidance on the evolution of the disease.